2021
DOI: 10.1021/acs.jmedchem.1c00631
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Targeting Serine/Threonine Protein Phosphatases with Small Molecules in Cancer

Abstract: Among numerous posttranslational regulation patterns, phosphorylation is reversibly controlled by the balance of kinases and phosphatases. The major form of cellular signaling involves the reversible phosphorylation of proteins on tyrosine, serine, or threonine residues. However, altered phosphorylation levels are found in diverse diseases, including cancer, making kinases and phosphatases ideal drug targets. In contrast to the success of prosperous kinase inhibitors, design of small molecules targeting phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 202 publications
(427 reference statements)
0
14
0
Order By: Relevance
“…Some small molecules have been identified that allosterically activate PP2A directly and are termed small molecule activators of PP2A (SMAPs). 296 , 297 Phenothiazines and perphenazine were discovered to activate PP2A and dephosphorylate some of its targets, such as AKT. 298 , 299 Iterative rounds of synthesis and optimization have since led to the development of several SMAPs.…”
Section: Progress In Innovative Pharmacological Approaches That Targe...mentioning
confidence: 99%
“…Some small molecules have been identified that allosterically activate PP2A directly and are termed small molecule activators of PP2A (SMAPs). 296 , 297 Phenothiazines and perphenazine were discovered to activate PP2A and dephosphorylate some of its targets, such as AKT. 298 , 299 Iterative rounds of synthesis and optimization have since led to the development of several SMAPs.…”
Section: Progress In Innovative Pharmacological Approaches That Targe...mentioning
confidence: 99%
“…Phosphorylation of proteins occurs most commonly at serines and threonines, where protein kinases transfer phosphate groups to these amino acid residues, usually using adenosine triphosphate as a substrate, and protein phosphatases hydrolyze phosphate from the amino acid residues of the protein. They collaborate to regulate protein function, stability, and signaling, as well as carrying out physiopathological tasks ( 85 ). Protein kinase C (PKC) isozymes are a group of serine/threonine kinases whose activity and levels are dispensed in several pathological heart conditions, including atherosclerosis (AS), myocardial infarction (MI), acute ischaemic, cardiac hypertrophy, cardiac arrhythmia, HF, and cardiac fibrosis ( 86 , 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serine/threonine kinases (STKs), a group of approximately 125 protein kinases that phosphorylate serines or threonines, are capable of maintaining cellular homeostasis, regulating the cell signaling pathway, and participating in cell proliferation, apoptosis, and metabolism by phosphorylating nuclear effectors, transcription factors, and cell cycle regulators. [5][6][7][8] STK16 is a myristoylated and palmitoylated STK that participates in the regulation of a wide array of cellular processes. 9,10 Previous studies have indicated that STK16 knockdown or kinase inhibition leads to cytokinesis arrest, thus affecting cell growth and apoptosis.…”
Section: Introductionmentioning
confidence: 99%